Prognostic significance of bi/oligoclonality in childhood acute lymphoblastic leukemia as determined by polymerase chain reaction - Scrideli, Carlos Alberto; Defavery, Ricardo; Bernardes, José Eduardo; Tone, Luíz Gonzaga (São Paulo Medical Journal, 2001)
CONTEXT: The CDR-3 region of heavy-chain immu- noglobulin has been used as a clonal marker in the study of minimal residual disease in children with acute lymphoblastic leukemia. Southern blot and polymerase chain reaction studies have demonstrated the occurrence of bi/oligoclonality in a variable number of cases of B-lineage acute lymphoblastic leukemia, a fact that may strongly interfere with the detection of minimal residual disease. Oligoclonality has also been associated with a poorer prognosis and a higher chance of relapse. OBJECTIVES: To correlate bi/oligoclonality, detected by polymerase chain reaction in Brazilian children with B-lineageacutelymphoblasticleukemiawith achance of relapse, with immunophenotype, risk group, and disease-free survival. DESIGN: Prospective study of patients’ outcome. SETTING: Pediatric Oncology Unit of the University Hospital, Faculty of Medicine of Ribeirão Preto, University of São Paulo. PARTICIPANTS: 47 children with acute lymphoblastic leukemia DIAGNOSTIC TEST: Polymerase chain reaction using consensus primers for the CDR-3 region of heavy chain immunoglobulin (FR3A, LJH and VLJH) for the detection of clonality. RESULTS: Bi/oligoclonality was detected in 15 patients (31.9%). There was no significant difference between the groups with monoclonality and biclonality in terms of the occurrence of a relapse (28.1% versus 26.1%), presence of CALLA+ (81.2% versus 80%) or risk group (62.5% versus 60%). Disease-free survival was similar in both groups, with no significant difference (p: 0.7695). CONCLUSIONS: We conclude that bi/oligoclonality was not associated with the factors investigated in the present study and that its detection in 31.9% of the patients maybe important for the studya nd monitoring of minimal residual disease.